1996
DOI: 10.1007/bf00232980
|View full text |Cite
|
Sign up to set email alerts
|

Intron-mediated enhancement of gene expression in maize (Zea mays L.) and bluegrass (Poa pratensis L.)

Abstract: We report a strength comparison of a large variety of monocot and dicot intron-containing fragments inserted in the 5' untranslated leader, between the CaMV 35S promoter and the uidA gene (coding for the ß-glucuronidase: GUS). Relative strengths of the intron-containing fragments were evaluated by comparing transient GUS expression after particle bombardment in embryogenic maize and bluegrass suspension cultures. Our results confirm a dramatic dependence on the presence of an intron for chimeric gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…Some dicot introns can elevate expression in a monocot (Vain et al, 2004), suggesting that IME signals are conserved across species. To test this, we evaluated the 12 Arabidopsis introns with measured effects on TRP1:GUS expression using an IMEter that had been trained with rice (Oryza sativa) introns.…”
Section: Rice Intronsmentioning
confidence: 99%
“…Some dicot introns can elevate expression in a monocot (Vain et al, 2004), suggesting that IME signals are conserved across species. To test this, we evaluated the 12 Arabidopsis introns with measured effects on TRP1:GUS expression using an IMEter that had been trained with rice (Oryza sativa) introns.…”
Section: Rice Intronsmentioning
confidence: 99%
“…The observation that some introns stimulate gene expression was first made in animal systems and extended to plants when Callis et al (1987) demonstrated that the maize (Zea mays) Adh1 first intron increased expression of several genes. Other maize introns that have been shown to increase expression include the Bz1 intron (Callis et al, 1987), Hsp82 first intron (Silva et al, 1988), Sh1 first intron (Vasil et al, 1989), Adh1 introns 2 and 6 (Mascarenhas et al, 1990), actin third intron (Luehrsen and Walbot, 1991), GapA1 first intron (Donath et al, 1995), Ubi1 first intron (Vain et al, 1996), and the RpoT fourth intron (Bourdon et al, 2001).Plant introns that stimulate expression have been documented in petunia (Petunia hybrida; Dean et al, 1989;Vain et al, 1996) Leon et al, 1991;Fu et al, 1995aFu et al, , 1995b, Arabidopsis (Rose and Last, 1997; ChaubetGigot et al, 2001), soybean (Glycine max; Kato et al, 1998), and tobacco (Nicotiana tabacum; Plesse et al, 2001). The approximately 2-to 10-fold range of intron-mediated enhancement usually seen in dicots is much less than increases observed in monocots, which can be more than 100-fold (for review, see Simpson and Filipowicz, 1996).…”
mentioning
confidence: 99%
“…The observation that some introns stimulate gene expression was first made in animal systems and extended to plants when Callis et al (1987) demonstrated that the maize (Zea mays) Adh1 first intron increased expression of several genes. Other maize introns that have been shown to increase expression include the Bz1 intron (Callis et al, 1987), Hsp82 first intron (Silva et al, 1988), Sh1 first intron (Vasil et al, 1989), Adh1 introns 2 and 6 (Mascarenhas et al, 1990), actin third intron (Luehrsen and Walbot, 1991), GapA1 first intron (Donath et al, 1995), Ubi1 first intron (Vain et al, 1996), and the RpoT fourth intron (Bourdon et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CaMV 35S promoter:mGFP5-ER:SPA terminator) of pGVT1 (Thole and Rawsthorne, 2003) into the NotIClaI-digested pGreenII0000 and by replacing the approximately 800-nt-long CaMV 35S promoter with the approximately 430-nt-long CaMV 35S promoter of pGVT5 (Thole and Rawsthorne, 2003). Subsequently, the CaMV 35S promoter:maize shrunken1-intron1:HPT:NOS terminator expression unit (Vain et al, 1996) was introduced into the SphI-digested pCLEAN-G90 to produce pCLEAN-G115. The blunted SalI-SpeI fragment of pCLEAN-G90 (i.e.…”
Section: Construction Of Pclean-g and Pclean-s Vectorsmentioning
confidence: 99%